Assessing Impact of PG Diploma in Inland Fisheries and Aquaculture Management on Trainee’s Job Performance - Beemalla Samatha; Argade, Dr. Shivaji; Ananthan P.S.; Karthireddy Syamala; Naila Majid Bhat (Journal of Indian Fisheries Association, 2023)
Skill development is the process of identifying people's skill gaps and addressing them with training and employment opportunities. This study aims to determine the effectiveness of CIFE's one year certificate course. An ex-post facto study was conducted with a structured interview schedule through the telephonic interview method. A four-level Kirkpatrick model comprising reaction, learning, behaviour, and results was used to evaluate the effectiveness of the course. According to the findings, the overall effectiveness mean unit score of the programme was 0.79, implying that the course was highly effective. The study emphasized the primary training needs perceived by the trainees. As a result, the study points out the significance of organising training in these areas. The medium level of skill development course effectiveness at behaviour level implies that the ICAR-CIFE needs to develop strategies for improving the effectiveness of the skill development program at behaviour level of trainees so that the applicability of learned knowledge and skills can be ensured. The trainees recommended lengthening the course duration from one year to two years and converting it into a diploma program to increase its demand and employment value. These findings will aid in increasing the effectiveness of ICAR-CIFE’s skill development training program in future and its impact on trainees' job performance